2014
DOI: 10.1080/02619768.2014.968705
|View full text |Cite
|
Sign up to set email alerts
|

Practicum experiences as sources of pre-service teachers’ self-efficacy

Abstract: This study examines physical education pre-service teachers' (PTs) self-efficacy and practicum experiences as self-efficacy sources through a mixed-method approach. For the quantitative phase, a self-efficacy questionnaire was applied to 141 PTs. Results showed a stronger self-efficacy in the relationship with students and discipline promotion. Lower self-efficacy was linked to instructional strategies. Concerning the qualitative phase, eight PTs were interviewed. PTs with higher self-efficacy reported profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 34 publications
4
50
1
8
Order By: Relevance
“…Martins, Costa and Onofre 35 , found that students studying PE tend to perceive themselves to be more effective when they are closer to the end of the course due to new experiences in teaching. Studies conducted by Zach, Harari and Harari 34 , found this trend in the evolution of TSE with 203 university students studying Physical Education.…”
Section: Discussionmentioning
confidence: 96%
“…Martins, Costa and Onofre 35 , found that students studying PE tend to perceive themselves to be more effective when they are closer to the end of the course due to new experiences in teaching. Studies conducted by Zach, Harari and Harari 34 , found this trend in the evolution of TSE with 203 university students studying Physical Education.…”
Section: Discussionmentioning
confidence: 96%
“…Personal teaching efficacy is defined as a belief in an individual's own ability to teach effectively, while teaching outcome expectancy is a belief that effective teaching will affect pupils' learning positively regardless of external factors (Enochs, Smith, & Huinker, 2000). Research on teacher efficacy indicates that it influences teachers' behaviours such as persistence on a task, risk taking, use of innovations and of more student-centered teaching strategies, effort invested in teaching and the goals they set, and greater enthusiasm and commitment for teaching (Enochs, Smith, & Huinker, 2000;Gavora & Wiegerová, 2017;Martins, Costa & Onofre, 2015;Tschannen-Moran & Hoy, 2001). Teacher efficacy is also related to student outcomes such as achievement and motivation (Tschannen-Moran & Hoy, 2001).…”
Section: Teacher Efficacymentioning
confidence: 99%
“…A series of immersive events targeted at progressively developing preservice teachers' confidence in teaching is essential before the preservice teacher begins an internship in a school. When preservice teachers perceive an experience as successful, especially when a difficult task is surmounted with little assistance or is achieved with few setbacks, their sense of confidence will increase (Bandura, 1997;Martins, Costo, & Onofre, 2015;Tschannen-Moran, Hoy, & Hoy, 1998). This suggests that preservice teachers must be given the opportunity to be successful in teaching before they are required to teach alone in schools where they are assigned to do their practicum.…”
Section: The Framework: Microteachingmentioning
confidence: 99%